2009
DOI: 10.1172/jci38902
|View full text |Cite
|
Sign up to set email alerts
|

The type III histone deacetylase Sirt1 is essential for maintenance of T cell tolerance in mice

Abstract: Although many self-reactive T cells are eliminated by negative selection in the thymus, some of these cells escape into the periphery, where they must be controlled by additional mechanisms. However, the molecular mechanisms underlying peripheral T cell tolerance and its maintenance remain largely undefined. In this study, we report that sirtuin 1 (Sirt1), a type III histone deacetylase, negatively regulates T cell activation and plays a major role in clonal T cell anergy in mice. In vivo, we found that loss o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
288
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(303 citation statements)
references
References 64 publications
13
288
2
Order By: Relevance
“…S6B), suggesting that Sirt1 inhibition promotes the survival of activated T cells. These results are consistent with the finding that loss of Sirt1 increases T-cell activation (26). Treatment with the Sirt1 inhibitors, but not with NAD + , increased the viability of Batf +/+ CD8 T cells stimulated with anti-CD3/CD28+IL-12 ( Fig.…”
Section: Batf Promotes Histone Acetylation Of the T-bet Locussupporting
confidence: 91%
See 1 more Smart Citation
“…S6B), suggesting that Sirt1 inhibition promotes the survival of activated T cells. These results are consistent with the finding that loss of Sirt1 increases T-cell activation (26). Treatment with the Sirt1 inhibitors, but not with NAD + , increased the viability of Batf +/+ CD8 T cells stimulated with anti-CD3/CD28+IL-12 ( Fig.…”
Section: Batf Promotes Histone Acetylation Of the T-bet Locussupporting
confidence: 91%
“…Although Sirt1 has been reported to modulate T-cell activation (26), the administration of Sirt1 inhibitors or activators is associated with many side effects because Sirt1 is expressed in many cell types. Because BATF expression is restricted to activated lymphocytes, BATF may be a promising therapeutic target to control effector T-cell generation for vaccine development and immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is required to maintain T-cell tolerance [61]. And the lack of SIRT1 resulted in hyperacetylation of c-Jun and the breakdown of T cell tolerance [62]. Therefore, the decreased activity of SIRT1 in aged people and RA patients may result in the activation of autoimmune T cells.…”
Section: Sirt1mentioning
confidence: 99%
“…In a recent study, Gao and coworkers showed that c-Jun transcriptional activity can be downregulated by SIRT1 in vitro [37]. A second study rapidly followed, showing that c-Jun is actively deacetylated by SIRT1 in vivo [38], while a third team reported that both the subunits c-Jun and c-Fos are targeted by SIRT1 [39]. These events play a major role in regulating the function of several immune cells.…”
Section: Sirt1 Inhibits Ap-1 By Deacetylating C-jun and C-fosmentioning
confidence: 99%
“…In T lymphocytes, AP-1 deacetylation by SIRT1 underlies T cell anergy and permits peripheral tolerance, preventing uncontrolled T cell proliferation and cytokine production [38]. As a consequence, SIRT1 -/-mice display an increased T cell responsiveness in vitro and Page 10 of 28 A c c e p t e d M a n u s c r i p t 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 are predisposed to develop autoimmune disorders, a conclusion further confirmed by an independent study [40].…”
Section: Sirt1 Inhibits Ap-1 By Deacetylating C-jun and C-fosmentioning
confidence: 99%